Public acceptance of banana leaf-filtered cloth masks as an alternative for medical masks - Mohamad Saifudin Hakim; Fitra Duhita; Mumtihana Muchlis; Rita Dian Pratiwi (Journal of Community Empowerment for Health, 2022)
One of the most basic control measures to prevent transmission of Coronavirus Disease 2019 (COVID-19) is that everyone should wear face masks wherever there are potential exposures such as public spaces and when there are suspected symptoms of COVID-19 infection. In addition to adherence to public safety protocols, community compliance in wearing face masks is mainly influenced by the comfort when the masks are worn. Several mask developments have been made to improve the comfort and function of the masks, including a modified cloth mask with a banana leaf filter. This study aimed to assess the public acceptance of this modified mask that we previously developed. We conducted a survey using an adaptation of the instrument called, the Usefulness, Satisfaction and Ease of Use (USE) questionnaire. The respondents consisted of 99 people from the Family Welfare Program and Islamic study group members in Tlogoadi, Sleman. The data analysis was conducted descriptively. The majority of the respondents agreed that the banana leaf-filtered cloth masks were useful, easy to use, and satisfying to be worn. The highest indicators were ease of use (83%) and satisfaction (83%). However, only a small percentage (30%) of respondents were interested in making their own homemade masks.